Impact of concomitant treatment of non-chronic total occlusion lesions at the time of chronic total occlusion intervention. (15th January 2020) - Xenogiannis, Iosif; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Jaffer, Farouc A.; Yeh, Robert W.; Patel, Mitul; Mahmud, Ehtisham; Choi, James W.; Burke, M. Nicholas; Doing, Anthony H.; Dattilo, Phil; Toma, Catalin; et al.
Abstract: Background: During chronic total occlusion (CTO) percutaneous coronary intervention (PCI), sometimes non-CTO lesions are also treated. Methods: We compared the clinical and procedural characteristics and outcomes of CTO PCIs with and without concomitant treatment of a non-CTO lesion in a contemporary multicenter CTO registry. Results: Of the 3598 CTO PCIs performed at 21 centers between 2012 and 2018, 814 (23%) also included PCI of at least one non-CTO lesion. Patients in whom non-CTO lesions were treated were older (65 ± 10 vs. 64 ± 10 years, p  = 0.03), more likely to present with an acute coronary syndrome (32% vs. 23%, p  < 0.01), and less likely to undergo PCI of a right coronary artery (RCA) CTO (46% vs. 58%, p  < 0.01). The most common non-CTO lesion location was the left anterior descending artery (31%), followed by the circumflex (29%) and the RCA (25%).Combined non-CTO and CTO-PCI procedures had similar technical (88% vs. 87%, p  = 0.33) and procedural (85% vs. 85%, p  = 0.74) success and major in-hospital complication rates (3.4% vs. 2.7%, p  = 0.23), but had longer procedure duration (131 [88, 201] vs. 117 [75, 179] minutes, p  < 0.01), higher patient air kerma radiation dose (3.0 [1.9, 4.8] vs. 2.8 [1.5, 4.6] Gray, p  < 0.01) and larger contrast volume (300 [220, 380] vs. 250 [180, 350] ml, p  < 0.01). Conclusions: Combined CTO PCI with PCI of non-CTO lesions is associated with similar success and major in-hospital complication rates compared with cases in which only CTOs were treated, but requires longer procedure duration and higher radiation dose and contrast volume. Highlights: In 23% of CTO PCI cases at least one non-CTO PCI takes place. Combined CTO plus non-CTO PCIs had similar success and in-hospital MACE rates compared with only-CTO PCIs. Combined cases, however, had longer procedure duration, and higher radiation dose and contrast volume.